COMPARATIVE ANALYSIS OF APPROACHES TO WORLD CONCEPTS: SPOD SOCIETY, VUCA SOCIETY AND BANI SOCIETY - Zakharov, Yevhenii (Social Economics, 2022)
The author of this study conducts a comparative analysis of several modern approaches to world concepts that replaced each other. Such concepts of the world include: SPOD society, VUCA society and BANI society. Starting proposed research with the description of each approach, the author gradually understands their essence by revealing their abbreviation, where each letter carries a certain meaning of the concept. SPOD is an acronym that characterizes a steady, predictable, ordinary and defined world and the society that lives in it. In 1987, the fundamentally new concept of VUCA society, which is characterized by a volatile, uncertain, complex, ambiguous state of the world replaced the SPOD of society. The next concept – BANI concept of society became relevant after loud, total events – with the onset of the pandemic period of COVID-19 in 2020 and people deciphered it as a brittle, anxious, non-linear and incomprehensible world (when the world had not previously faced a pandemic of this scale), despite the fact that the signs of VUCA society also remained present in the world. The specific characteristics of the subject, object and purpose of the scientific article determine the choice of research methods. To study approaches to world concepts, the author used the method of generalization, analysis and synthesis, classification methods, comparative analysis, inductive and deductive methods for the author to generalize the obtained data.. After conducting research, the author of article comes to the certain conclusions that the above approaches (namely SPOD, VUCA and BANI) are rather a reaction to events that occurred in one or another period of time than actual solutions. The benefit of this research lies in its informativeness, generalization of approaches to world concepts. The information from this research allows companies to better understand the world in which they live and the society in which they do business.